Jewish Refugee Physicians in Prince Edward Island during the 1940s - Glass, Joseph B. (Canadian Jewish Studies / Études juives canadiennes, 2024)
The province of Prince Edward Island faced an acute shortage of physicians during World War II. The supply of doctors was limited for two primary reasons: enlistments in the Canadian armed forces; and an aging workforce nearing or entering retirement. The province turned to other sources to fill these gaps. An unexpected supply was European Jewish refugee physicians who fled before and during the war and eventually reached Canada. Despite the federal government’s opposition to Jewish immigration, and the Canadian Medical Association’s resistance to accepting refugee physicians, seven Jewish physicians practiced in PEI for varying length of time. This article reviews the medical services in PEI during the late 1930s and 1940s, efforts to alleviate the shortage of doctors, and attitudes towards Jewish refugee doctors and the roles of various stakeholders in facilitating or hindering their arrival. The article further explores how these refugee physicians’ stories contributed to the province’s health services, as well as their social and cultural integration into local society.